Зображення скіфського музиканта на сахнівській пластині - Олійник, О.Г. (Археологія, 2003)
Статтю присвячено аналізу музичного інструмента та інтерпретації образу музиканта. В статье дан анализ особенностей формы и конструкции струнного музыкального инструмента. Рассмотрены проблемы, связанные с его типологией и этнической принадлежностью. Предложенная семантическая интерпретация формы и украшений инструмента в совокупности с ранее не привлекавшимися источниками позволяет пересмотреть общепризнанное структурно-композиционное построение центрального мотива пластины и предположить, что на оригинале, послужившем «матрицей» для оттиска пластины, музыкант был выделен в самостоятельный мотив, имеющий важное значение для раскрытия содержания всей композиции. The article deals with analysis of peculiarities of shape and construction of a string musical instrument. The problems, connected with its typology and belonging to the definite ethno-cultural midst are also considered in the article. Suggested semantic interpretation of shape and ornamentation of instrument on the ground of sources, which had not been analyzed before, enables the specification of the complete interpretation of the central plot of the composition on the plate. The supposition have been done that on the original one, which had served the “matrix” for the impression of the plate, the musician was included into the separate motif, which had the important meaning for discovering the contents of the whole composition.